2017
DOI: 10.1016/j.tsf.2017.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Progression of reduction of MoO3 observed in powders and solution-processed films

Abstract: Understanding the reduction of MoO3 is important for the utilization of this material in optoelectronic applications. Here, we examine the changes that take place during reduction of a solution-processed thin film of MoO3. Upon reduction in dilute hydrogen gas, the nanocrystallite grain morphology is observed hosting a sequence of shear defects, nucleation and growth of reduced molybdenum oxide phases within the MoO3 matrix before decomposition of the film. The compositional changes are tracked and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…In the case of the SCM and SMC designs, E gap drops in the same range from 2.74 to 2.60 eV and from 2.82 to 2.70 eV, respectively (see Figure a). For MoO 3 thin films, the slight increase in E gap with the annealing temperature has also been observed by other groups, which have deposited this oxide by different synthesis techniques. This effect has been associated with a structural rearrangement of the MoO 3 lattice, specifically a reduction of point defects . In addition, our group recently found that the crystallization process in MoO 3 takes place at higher temperatures, with respect to annealing in air, when the thermal treatments are performed in inert atmospheres. , This information implies that, for the SMC system, the CdSe layer causes a slow rearrangement process in the MoO 3 lattice as compared to the case where MoO 3 is directly exposed to oxygen.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In the case of the SCM and SMC designs, E gap drops in the same range from 2.74 to 2.60 eV and from 2.82 to 2.70 eV, respectively (see Figure a). For MoO 3 thin films, the slight increase in E gap with the annealing temperature has also been observed by other groups, which have deposited this oxide by different synthesis techniques. This effect has been associated with a structural rearrangement of the MoO 3 lattice, specifically a reduction of point defects . In addition, our group recently found that the crystallization process in MoO 3 takes place at higher temperatures, with respect to annealing in air, when the thermal treatments are performed in inert atmospheres. , This information implies that, for the SMC system, the CdSe layer causes a slow rearrangement process in the MoO 3 lattice as compared to the case where MoO 3 is directly exposed to oxygen.…”
Section: Resultssupporting
confidence: 63%
“…30−32 This effect has been associated with a structural rearrangement of the MoO 3 lattice, specifically a reduction of point defects. 30 In addition, our group recently found that the crystallization process in MoO 3 takes place at higher temperatures, with respect to annealing in air, when the thermal treatments are performed in inert atmospheres. 25,33 This information implies that, for the SMC system, the CdSe layer causes a slow rearrangement process in the MoO 3 lattice as compared to the case where MoO 3 is directly exposed to oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of reduced phases is in agreement with a previous work on the progression of reduction of MoO3. 58 It should be noted that the band gaps given by the Tauc analysis in the previous work include the contributions from the sub-band gap states, such that the Tauc band gap decreases with the onset of reduced phases. Here, the optical analysis accounts for the sub-band gap states with the Gaussian oscillator.…”
Section: Resultsmentioning
confidence: 93%
“…Formation of these reduced species involves a lattice rearrangement from corner-shared octahedra to an edge-shared octahedra with a shear structure. , Spevack and McIntyre reported that temperatures near 730 °C were required in order to reduce MoO 3 thin films, originally synthesized at a low temperature (250 °C), to MoO 2 . Inzani and co-workers investigated the reduction of MoO 3 powders and solution-processed films under dilute (5%) hydrogen gas. Shear defects, nucleation, and growth of reduced phases within the MoO 3 matrix were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2,19 Spevack and McIntyre 19 reported that temperatures near 730 °C were required in order to reduce MoO 3 thin films, originally synthesized at a low temperature (250 °C), to MoO 2 . Inzani and co-workers 20 MoO 3 powders and solution-processed films under dilute (5%) hydrogen gas. Shear defects, nucleation, and growth of reduced phases within the MoO 3 matrix were investigated.…”
Section: ■ Introductionmentioning
confidence: 99%